(untitled) (Economic and Political Thought, 2014)
The existence of state borders is a condition for establishing the territory of a state, the range of authority and the population that is subject to it. Thus, determining borderlines is an essential element of the establishment of statehood. Unfortunately, in case of Ukraine, that element has not been implemented, especially as far as the borderline with Russia is concerned. The first Ukrainian sovereign attempts to establish its eastern border failed when the Bolsheviks led their army on the march to Warsaw in June 1920. For the next 70 years, the almost 2,300 km long Ukrainian-Russian border remained an internal administrative one. After 1991, then independent Ukraine started to make the effort to be internationally recognised. The most important elements of that were its bilateral agreements with Russia. At the turn of the century, the approval of the eastern Ukrainian border in the form of a treaty by the biggest neighbour was finally achieved, however, its actual status was defective because of the lack of demarcation lines and a shortage of personnel, border infrastructure or monitoring equipment. Problems with the protection of the Ukrainian-Russian border to a large extent facilitated Russian aggression begun in March 2014. In order to understand the difficulties with separating the two countries, it is necessary to take into account strong economic and social links between the societies on the two sides of the border who used to live in one state for a few centuries.